Analisis Pengaturan Hukum Acara Kepailitan dan Penundaan Kewajiban Pembayaran Utang - Doni Budiono (ADHAPER: Jurnal Hukum Acara Perdata, 2018)
In carrying out its business, businessmen often establish a debt agreement. Debt agreements are a common thing between creditors and debtors. However, at times, it may cause a dispute between debtors who are negligent and unable to pay their debts to creditors. One of the eﬀ orts to overcome the unpaid debt is through Bankruptcy and Postponement of Debt Payment Obligations petitioned by the debtors or the creditors. Bankruptcy is the general seizure of all the assets of a bankrupt debtor whose management and settlement is carried out by the Curator under the supervision of the Supervisory Judge. On the other hand, Postponement of Debt Payment Obligations (PKPU) is the settlement of the debt, also aiming to establish a peace oﬀ er that includes oﬀ ers of partial payment or whole payment of the debt to the creditors. Bankruptcy and PKPU in its implementation have been regulated in Indonesian Law Number 37 of 2004 on Bankruptcy and Postponement of Debt Payment Obligations, Herziene Indonesisch Reglement (HIR), Reglement of De Rechtsvordering (Rv), Buitengewesten Rechtsreglement (RBg), and further stipulated in the Civil Law Procedure-Draft. In Bankruptcy and Postponement of Debt Payment Obligation’s procedural law arrangements contained in various regulations and in the Civil Law Procedure-Draft, there are shortcomings that need to be analyzed to provide a legal basis for Bankruptcy and Postponement of Debt Payment Obligations procedural law arrangements. Considering the upcoming legalization of the Civil Law Procedure-Draft, this study will analyze several important points that can be used as a reference for the Civil Law Procedure-Draft.